Exome sequencing of 112 trios identifies recessive genetic variants in brain arteriovenous malformations. (26th August 2020) - Zhang, Mingqi; Ding, Xinghuan; Zhang, Qianqian; Liu, Jian; Zhang, Yisen; Zhang, Ying; Tian, Zhongbin; Li, Wenqiang; Zhu, Wei; Kang, Huibin; Wang, Zhongxiao; Wu, Xinzhi; et al.
Abstract : Background: Brain arteriovenous malformation (BAVM) is a main cause of cerebral hemorrhage and hemorrhagic stroke in adolescents. Morphologically, a BAVM is an abnormal connection between cerebrovascular arteries and veins. The genetic etiology of BAVMs has not been fully elucidated. In this study, we aim to investigate potential recessive genetic variants in BAVMs by interrogation of rare compound heterozygous variants. Methods: We performed whole exome sequencing (WES) on 112 BAVM trios and analyzed the data for rare and deleterious compound heterozygous mutations associated with the disease. Results: We identified 16 genes with compound heterozygous variants that were recurrent in more than one trio. Two genes ( LRP2, MUC5B ) were recurrently mutated in three trios. LRP2 has been previously associated with BAVM pathogenesis. Fourteen genes ( MYLK, HSPG2, PEAK1, PIEZO1, PRUNE2, DNAH14, DNAH5, FCGBP, HERC2, HMCN1, MYH1, NHSL1, PLEC, RP1L1 ) were recurrently mutated in two trios, and five of these genes ( MYLK, HSPG2, PEAK1, PIEZO1, PRUNE2 ) have been reported to play a role in angiogenesis or vascular diseases. Additionally, abnormal expression of the MYLK protein is related to spinal arteriovenous malformations. Conclusion: Our study indicates that rare recessive compound heterozygous variants may underlie cases of BAVM. These findings improve our understanding of BAVM pathology and indicate genes for functional validation.